Effective dose and persistence of Rhodamine‐B in wild pig Vibrissae. (1st December 2017) - Webster, Sarah C.; Cunningham, Fred L.; Kilgo, John C.; Vukovich, Mark; Rhodes, Olin E.; Beasley, James C.
ABSTRACT: As a result of substantial ecological and economic damage attributed to wild pigs ( Sus scrofa ), there is international interest in using pharmaceutical baits to control populations. To assess the efficacy and specificity of baiting programs, chemical biomarkers can be used to evaluate uptake of pharmaceutical baits. Rhodamine B (RB) is known to be an effective biomarker in wild pigs. However, significant data gaps exist regarding the minimum effective dosage and persistence of RB in wild pigs. We used a controlled double‐blind study experiment conducted in spring of 2014 on the Savannah River Site, Aiken, South Carolina, USA, wherein we administered a one‐time dose of RB at 3 treatment levels (5 mg/kg, 15 mg/kg, or 30 mg/kg) to 15 captive pigs, with 5 pigs/treatment group to investigate persistence of RB. Facial vibrissae were collected pre‐RB ingestion as a control and every 2 weeks post‐RB ingestion for 12 weeks. We examined samples for RB presence and used a generalized linear mixed model (GLMM) to determine the influence of treatment dose on persistence of RB. Additionally, we measured distance moved by the RB mark away from the vibrissae root and used a GLMM to assess movement rates of RB bands along growing vibrissae. We found consistently greater persistence of RB in the 15‐ and 30‐mg/kg treatments across the sampling period. A significant, positive movement trend in RB bands was observed within the 15 mg/kg and 30 mg/kg groups. Based on our results, a 15 mg/kg dosage can be considered a minimum effective dose for wild pigs and will reliably produce a detectable RB mark up to and likely beyond 12 weeks after ingestion. © 2017 This article is a U.S. Government work and is in the public domain in the USA. Abstract : Rhodamine B (RB) can be used to assess the efficacy and specificity of pharmaceutical baiting programs; however, data gaps exist regarding the minimum effective dose and persistence of RB in wild pigs. We found that a 15 mg/kg dosage was the minimum effective dose for wild pigs and will reliably produce a detectable RB mark up to and likely beyond 12 weeks after ingestion.